Gluteal muscle activation during rehabilitation exercises in female field hockey players - Daretha Coetzee; Frederik F. Coetzee; Robert Schall; Colleen Sinclair (AOSIS, 2021)
Background: Field hockey, a team sport played by both men and women at both recreational and professional levels, requires maintaining a forward flexed posture putting stress on the lumbar spine. Hence, it is necessary to assess the muscles supporting the lumbar spine, especially those surrounding the hip, to inform strengthening exercises for this population. Objectives: To establish the best body weight rehabilitation exercises shown to produce high muscle activation (≥ 61%MVIC - maximal voluntary isometric contraction) for both the gluteus maximus (Gmax) and medius (Gmed) muscles. Four exercises fell into this category. Method: Surface electromyography (sEMG) was used to record the muscle activation of Gmax and Gmed of four body weight rehabilitation exercises in 26 high-performance female field hockey players. The %MVIC activation data of both Gmax and Gmed were analysed using a three-way ANOVA. Results: The single-leg squat generated the highest %MVIC activation of both Gmax (125.65%MVIC) and Gmed (126.30%MVIC). The only statistically significant difference for Gmax was between the single-leg squat and plank with hip extension (p = 0.0487). No statistically significant difference was observed for Gmed between the four body weight rehabilitation exercises (p = 0.6285). Conclusion: The four exercises generated similar %MVIC activation levels. The single-leg squat produced the highest observed %MVIC of Gmax and Gmed in high-performance female field hockey players and is, therefore, recommended. Clinical implications: Implementation of the findings could result in benefits during prehabilitation, injury prevention programmes and the later stages of rehabilitation for high-performance female field hockey players.